The South American Advances in Submarine Canyons Studies and Their Link to the Ocean Decade - Silva, Marcos V. B.; Araújo, Tereza C. M. (Frontiers in Marine Science, 2021)
Submarine canyons have a relevant role in marine ecosystems. They are responsible for oceanographic conditions such as variability of temperature and salinity, sediment transport, nutrients, and even pollutants amongst marine areas. Submarine canyon studies have been growing and reaching prominence due to their importance in the Blue Economy. Initiatives to promote sustainable development for the ocean have been discussed in the Ocean Decade. Although canyons studies are increasing, how can we integrate these with the Ocean Decade outcomes? Thus, we aim to demonstrate an overview of the advances of submarine canyons studies and their link to the Ocean Decade for South America. We analyzed 160 studies divided into spatiotemporal analysis and study approaches according to the Ocean Decade outcomes. We discuss these articles, building a timeline and argumentative topics considering the advances, and discuss gaps to predict the future of submarine canyons studies in the Ocean Decade and Blue Economy context.